Delayed subarachnoid hemorrhage 7 years after cerebellar infarction from traumatic vertebral artery dissection. (19th July 2016) - Silva, Michael A; See, Alfred P; Khandelwal, Priyank; Patel, Nirav J; Aziz-Sultan, Mohammad Ali
Abstract : Vertebral artery dissection (VAD) is an important cause of ischemic stroke and subarachnoid hemorrhage (SAH). Dissections presenting with ischemia rarely cause SAH after more than a few hours, especially without radiographic evidence of pseudoaneurysm. We successfully treated a patient for persistent vessel injury presenting with SAH 7 years after presenting with extracranial subocclusive dissection of the right vertebral artery and an associated right posterior inferior cerebellar artery stroke. This is one of only three reported cases of delayed SAH occurring more than 2 weeks after an initial ischemic presentation of a VAD, and the only one without radiographic evidence of pseudoaneurysm at standard follow-up duration.